Structures and Mechanisms, The Chaos Theory and Organizational Change - Erez, Ofer; Cristal-Lilov, Anna; Salmon, Anat Ben (American Journal of Management, 2021)
A conceptualisation of personal epistemology was constructed drawing from the ‘structures and mechanisms’ of the Critical Realist theoretization and concepts of the chaos theory. Individuals can be viewed as an open system, within another open system of their environment, in which minute changes or fluctuations in the opening conditions, can cause unpredictable outcomes. Viewing organisations such as a University as open structures, the process of installing innovative knowledge into the academy was then examined in chaos theory terms. Open systems exist in a state of perpetual disequilibrium, being subject to constant fluctuations and autocatalysis, yet maintain stability. Since Universities strive to maintain stability by perpetuating traditional epistemologies and knowledge, introducing innovative knowledge is a challenge. A small team of researcher-practitioners conducted successive actions, intending to introduce a new epistemology and method, challenging the status quo. The University’s self-renewing dynamic, tried to suppress these fluctuations. The professional obligations of the practitioner-researchers motivate them to persist, until their actions will overcome the system’s ability to suppress them, and ‘second-order change’ will occur.